Isolation of Indigenous Azotobacter from the Soil of Different Regions of Tehran and Investigating the Effect of Their Inoculation on Tomato (Solanum lycopersicum L.) Plant Growth - Shaghayegh Golchin Irani; Gholamreza Taheri Sangsari; Akram Sadat Tabatabaee Bafroee; Mohammad Javad Avesta (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
Azotobacter is an aerobic, gram negative and chemoorganotrophic bacterium, that is able to stabilize molecular nitrogen nonsymbiotically. The role of Azotobacter in plant growth is due to the production of growth-promoting hormones, the ability to dissolve insoluble phosphates, nitrogen fixation, increase stress resistance and biocontrol of plant pathogens. The aim of this study was to isolate and identify the indigenous Azotobacter from the soil of different areas of Tehran. The effect of tomato plant inoculation with isolates on growth promoting was also investigated. Finally, the growth conditions of the superior isolate were optimized.  Azotobacter isolates were obtained from soil samples using serial dilution method and identified by conventional biochemical tests. The nif H gene, encoding nitrogenase enzyme, was identified in isolates using real-time PCR technique. Then the tomato seeds were inoculated with isolates and seedling growth rate including stem and root length were measured during 34 days. The parameters of temperature, pH, aeration rate, and carbon and nitrogen sources were optimized for superior isolate. In this study, 27 isolates were identified as nitrogen fixing Azotobacter. Considering the results, all isolates showed a significant increase (p <0.05) in stem and root length of tomato plants compared to standard strain and negative control. Among them, isolate No. 21 had the greatest effect during 34 days of study and its best growth conditions in the presence of mannitol carbon source, peptone nitrogen source, 200 rpm rotation, 30°C and pH 7were acquired. According to the results of this study, the obtained indigenous isolates particularly isolate No.21 have the potential to be used as biological fertilizer after further investigations.